Seasonal Variations in Superovulatory Response and Embryo Recovery in Buffaloes (Bubalus bubalis) - Matharoo, J S; Singh, Mehar (The Indian Journal of Animal Reproduction, 2023)
A total of 11 buffaloes (7 in winter and 4 in summer) were superovulated using follicle stimulating hormone (FSH-P). Flushing was done on day 5/6 using two-way German Catheter and Dulbecco’s phosphate buffered saline fortified with bovine serum albumin and antibiotics. Superovulatory response was observed to be better in winter (6.0±0.47 CL) than summer (3.0±0.40 CL). On an average 2.16±0.79 - embryos were recovered in winter as against 0.5±0.28 in summer. Based on morphology all of the embryos recovered in winter were of good/excellent quality whereas half of those recovered in summer were good and rest poor.